Modeling of Magnetic Field Influence on Electrophysical Effects in Magnetoimpedance Microwires - R.I. Shakirzyanov; V.A. Astakhov; A.T. Morchenko; P.A. Ryapolov (Журнал нано- та електронної фізики)
The pursuance of the research of dependency between magnetoimpedance effect and the distribution of magnetization relatively to amorphous ferromagnetic microwire axis is important for creating high-sensitive magnetic field sensors. Distribution of signal in skin-layer is considered as a function of the magnetic properties of the wire material, bias current flowing through it, strength and orientation of the external magnetic field. The impact of these factors on the signal of microwire with circumferential (helical) anisotropy is analyzed on the base of numerical simulation.